Estrategias psicopedagógicas para la inclusión de estudiante con tdah de educación básica - Velez Aguirre, Jazmin Antonia (2025)
This research examined the implementation of psychopedagogical strategies for the inclusion of students with Attention Deficit Hyperactivity Disorder (ADHD) in primary education, considering their impact on academic performance and social integration. It was based on the need to enhance inclusive education through effective strategies that enable these students to develop their potential in adapted school environments. The main objective was to identify and implement psychopedagogical strategies that facilitate the inclusion of students with ADHD in the classroom, promoting their active participation and optimizing their academic and social performance. A qualitative methodology was used, involving classroom observations, semi-structured interviews with teachers, families, and the student, as well as a documentary review of previous studies and educational regulations. The primary challenges in including students with ADHD were identified as a lack of teacher training, insufficient knowledge of appropriate strategies, and a shortage of adaptive resources in the classroom. In response, a psychopedagogical strategy was designed and implemented, incorporating curricular adaptations, positive reinforcement, multisensory teaching, and collaborative work with families and teachers. The results showed improvements in the student’s attention, self-regulation, and participation, facilitating their learning process and integration with peers. It was concluded that the effective inclusion of students with ADHD requires a comprehensive approach involving teachers, families, and psychopedagogical specialists. The study highlights the importance of teacher training and the adaptation of pedagogical strategies to meet the specific needs of these students.